Nilai emosional dan minat beli konsumen: Studi empiris pada platform Tiktok shop di indonesia - Pakpahan, Arnolt; Ekasari, Ayu; Chandra, Kristian (Nur Science Institute, 2026)
This study aims to analyze the influence of emotional value on consumers' buying interest on the TikTok Shop platform and to affirm the role of emotions in the social media-based purchase decision-making process. The study used a quantitative, survey-based approach among TikTok users who had interacted with sales content. Data was collected through an online questionnaire using a five-point Likert scale and analyzed using the Partial Least Squares (PLS) method with the help of SmartPLS software. The results showed that emotional value had a positive and significant effect on consumer buying interest, with the model's predictive ability being moderate to strong. These findings confirm that positive emotional experiences, such as happiness, satisfaction, and entertainment, are important drivers of purchase intent in the context of social commerce. The novelty of this research lies in the empirical testing of emotional value as the main determinant of buying interest in the TikTok Shop ecosystem using the PLS approach, which remains underdeveloped in digital marketing studies in Indonesia, as well as in the emphasis on shifting marketing strategies from rational aspects to consumer emotional experiences.